Structural-functional features of the heart in patients with acute Q-myocardial infarction of the anterior wall of the left ventricle in the presence of pulmonary hypertension - Syvolap, Victor; Zemlyaniy, Yaroslav (ScienceRise: Medical Science, 2019)
The aim was to evaluate the structural and functional features of the heart in the acute myocardial infarction (AMI) of the anterior wall of the left ventricle (LV) in the presence of pulmonary hypertension (PH) for the development of more informative diagnostic markers, forecast predictors and improved treatment of patients. Materials and methods. A total of 90 patients (53 men and 37 women) with acute myocardial infarction of the anterior wall of the LV (AMI AV) were examined in the intensive care unit for acute coronary insufficiency of the Communal Non-profit Enterprise "City Emergency and Ambulance Hospital" of the Zaporizhzhya City Council. Patients were divided into two groups: 55 patients with AMI AV with PH (mean age 70.65±1.83 years), 35 patients with AMI AV without HD (mean age 66.80±2.02 years). For all patients in the first three days after hospitalization, two-dimensional echocardiography was performed on the device "MyLab50" ("Esaote", Italy) according to the recommendations of the American Society of Echocardiography. For statistical data processing, statistical software package "Statistica 6.0 for Windows" (StatSoft Inc., № AXXR712D833214FAN5) was used. The reliability of the differences in the groups was evaluated using the dual t-criterion of the Student for independent samples. To assess the convergence of the indicators, the χ2 criterion, corrected by Yeats, was determined. The reliability of the differences between the indices was confirmed at p<0.05. Results. In patients with AMI AV with PH in comparison with patients with AMI AV without РH, there was a significant decrease in ejection fraction (22.3 %; p<0.05), increase in myocardial mass index (by 18.3 %, p<0.05) and end systolic diameter of left ventricle (12.4 %; p<0.05), dilatation of left atrium (by 11.6 % (p<0.05), right ventricle (by 27.3 %, p<0.05) and right atrium (by 20, 9 %; p<0.05). In assessing the types of remodeling of the of left ventricle, it was found that in patients with AMI AV with PH was predominantly eccentric hypertrophy (90.9 %), which is significantly higher in comparison with the AMI AV without PH. Patients with AMI AV and PH have a significant acceleration peak E of mitral valve (by 34.4 %; p<0.05), an increase in the ratio E/A of mitral valve (by 61.1 %, p <0.05), the time of isovolumetric relaxation LV extension (on 13.9 %; p<0.05) and acceleration peak E of tricuspidal valve E (by 28.3 %, p<0.05) in comparison with patients without PH. According to the data of tissue dopplerography, patients with AMI AV and PH showed an increasing ratio E/E’ of mitral valve (MV E/E’) (by 46.5 %; p<0.05) and ratio E/E’ of tricuspidal valve (TV E/E’) (by 39.3 %; p<0.05 ) compared with patients without PH. In patients with AMI AV and PH there was a predominant type of diastolic dysfunction (40 % of cases), type of diastolic dysfunction with disturbance of relaxation (71.4 %) predominated in the group of AMI AV without PH. Conclusions. In patients with AMI AV pulmonary hypertension develops against the background of dilation of the left chambers of the heart with the formation of eccentric hypertrophy and systolic dysfunction of the left ventricle, overloading of the right chambers of the heart with an increase in the size of the right atrium and left ventricle. Patients with AMI AV with PH had a predominantly pseudonormal type of LV diastolic dysfunction with an increase in MV E/E’ ratio and diastolic dysfunction of right ventricle, as evidenced by an increase in the ratio of TV E/E’